The Management Of The Education Operational Grant And Its Effects On School Development - Rismita, Rismita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The problem that has occurred in schools is in managing education operational aid funds in the current year is not in accordance with the recording of recapitulation of data for students who receive funds resulting in each area in use there is a difference or the remaining funds and less effective in managing expenditure per student by comparing school districts which is based on the previous year's budget that has already happened. This study aims to analyze the management of school fund management towards school development. The research method used is descriptive qualitative research by explaining the function of management. Data collection techniques in this study were interviews with the principal, deputy headmaster of the curriculum, the head of school administration, observation, and documents relating to the accountability of funds. The results of the study are grouping funds according to school programs, there is no waste of funds based on the percentage of funding funding per quarter. The Principal builds a system of monitoring the use of funds in an accountable and accurate manner in achieving the vision and mission of the school